2015
DOI: 10.1002/chem.201503293
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Catalysis: Calcium and Camphorsulfonic Acid Catalyzed Cycloisomerization of Diynols

Abstract: The first transition metal-free cycloisomerization of easily accessible diynols is presented as a novel approach to bicyclic 2H-pyrans. As a one-step protocol, the reaction proceeds in a single reaction cascade by intertwining mechanistic fragments borrowed from transition metal-catalyzed Claisen rearrangment of vinyl ethers with our own work on allenyl/propargyl cation rearrangements and a 6π-oxo-electrocylization. It is enabled by a new cooperative catalytic system that combines a simple Ca(2+) catalyst with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…In line with the model in Scheme , this highlights the important role of water and Li + cations. Among the many proton donors tested, camphorsulfonic acid (CSA, Table 1, entry 5; others not shown) slightly improves the results . The variation of the additives (e.g.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…In line with the model in Scheme , this highlights the important role of water and Li + cations. Among the many proton donors tested, camphorsulfonic acid (CSA, Table 1, entry 5; others not shown) slightly improves the results . The variation of the additives (e.g.…”
Section: Methodsmentioning
confidence: 98%
“…Ther egioselectivity of the addition is governed by the cation stabilizing effect of the a-aryl substituent. [24] Thev ariation of the additives (e.g.B u 4 NSbF 6 ,B u 4 NBF 4 ,e tc. In line with the model in Scheme 1, this highlights the important role of water and Li + cations.Among the many proton donors tested, camphorsulfonic acid (CSA, Table 1, entry 5; others not shown) slightly improves the results.…”
mentioning
confidence: 99%
“…Finally, other structural factors, such as annulation, also favor the 2HP form. It has been well established that annulation favors the closed form by restricting conformational freedom (entropic trap), and it has been used as a design element in the synthesis of stable 2HPs [26,27]. Scheme 6 graphically summarizes the main conclusions of these studies.…”
Section: Dienone/2hp Equilibriummentioning
confidence: 99%
“…In these cases, significant steric interactions disfavor planarity, and consequently, the π‐delocalization through the conjugated system. Studies on these equilibria have shown that the 2 H ‐pyran form is stabilized by the presence of electron‐withdrawing groups at the C‐5 position (R 5 in Scheme ; electronic factors), disubstitution at the C‐2 position (R 2 /R 2′ ≠ H)(steric factors) or annulation (entropic trap). Prototypical examples of stable 2 H ‐pyrans are 2 H ‐chromenes ( 1 ), 2,2,4‐trimethyl‐2 H ‐pyran ( 2 ) (favored by steric factors) and methyl 2,2‐dimethyl‐2 H ‐pyran‐5‐carboxylate ( 3 ) (favored by a combination of steric and electronic factors) (Scheme ).…”
Section: Introductionmentioning
confidence: 99%